2006
DOI: 10.1074/jbc.m609405200
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interaction of the p14ARF Tumor Suppressor with Ribosomes

Abstract: Alterations in the p14ARF tumor suppressor are frequent in many human cancers and are associated with susceptibility to melanoma, pancreatic cancer, and nervous system tumors. In addition to its p53-regulatory functions, p14 ARF has been shown to influence ribosome biogenesis and to regulate the endoribonuclease B23, but there remains considerable controversy about its nucleolar role. We sought to clarify the activities of p14 ARF by studying its interaction with ribosomes. We show that p14 ARF and B23 interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…In contrast, the p14ARF protein inactivates the MDM2 protein and thereby stabilizes the p53 protein, but also suppresses ribosome biogenesis. 37 Therefore, genetic alterations of the CDKN2A locus may impair both p14ARF/p53 and p16INK4A/pRb pathways, providing a selective advantage in the development and progression of tumors. In the present study, molecular anatomy of the deletions determined clearly indicated that in almost all cases, both p14ARF and p16INK4A are inactivated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the p14ARF protein inactivates the MDM2 protein and thereby stabilizes the p53 protein, but also suppresses ribosome biogenesis. 37 Therefore, genetic alterations of the CDKN2A locus may impair both p14ARF/p53 and p16INK4A/pRb pathways, providing a selective advantage in the development and progression of tumors. In the present study, molecular anatomy of the deletions determined clearly indicated that in almost all cases, both p14ARF and p16INK4A are inactivated.…”
Section: Discussionmentioning
confidence: 99%
“…S5), suggesting that the inhibition of VEGFA IRES activity may not be attributed to the defective rRNA maturation commonly observed in ARF-expressing and DKC1 m cells. p14 ARF was shown to inhibit global protein synthesis by interfering with polysome formation (40). Therefore, translational repression of VEGFA may merely reflect such global effects of ARF protein.…”
Section: Discussionmentioning
confidence: 99%
“…While 28S, 5.8S, 5S rRNA and large ribosomal proteins constitute (LRPs) the 60S subunit, the 40S subunit is composed by 18S rRNA and small ribosomal proteins (SRPs). Several oncogenes, like c-Myc, are able to enhance the production of ribosomal components, by the stimulation of all the three RNA Polymerases [69], while tumor suppressors like p14 ARF or p53, are able to bind and inhibit the activity of several transcription factors like SL1 and UBF, needed for Polymerase I transcription, leading to ribosome biogenesis inhibition [10, 11]. On the other hand, several alterations in ribosome biogenesis, such as rRNA transcription inhibition or rRNA processing impairment, lead to a coordinated induction of p53 activity.…”
Section: Introductionmentioning
confidence: 99%